Male Sexual and Reproductive Health in Diabetes and Obesity Pharmacotherapy: A Source‐Triangulated Counseling Map - Marek Broul; Michal Dubský; Aneta Hujová; Michaela Liegertová (Andrology, 2026)
ABSTRACT Background Drugs used for diabetes and obesity increasingly shape male sexual and reproductive counseling, but clinical studies, trial registrations, regulatory labels, and patents answer different questions. Objectives The objective is to map these sources and define what each can support when counseling men receiving metabolic drugs. Materials and Methods We reviewed human studies, ClinicalTrials.gov records, FDA/EMA labels, and selected patent or pipeline documents using source‐specific eligibility criteria and evidence rules. Results Human evidence is concentrated around glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs), dual GLP‐1/GIP receptor agonism, SGLT2 inhibitors, and metformin or paternal exposure. Direct fertility and live‐birth data remain sparse. Trial registries include more male reproductive endpoints than published studies report. Regulatory labels mainly inform genital‐safety counseling and nonclinical reproductive toxicology language. Patents contain erectile and male reproductive claims, but these claims are not clinical evidence. Discussion and Conclusion Counseling should separate genital safety, endocrine and sexual‐function signals, semen and fertility outcomes, and paternal‐exposure concerns. Hormonal, sexual‐function, or semen changes may track metabolic recovery; they do not establish improved conception or live birth. These drugs should be selected for metabolic indications, not as treatments for ED or infertility.